Substituted cyclopentannulated tetraazapentacenes [data] - Maier, Steffen (Universität, 2023)
Brominated pentannulated dihydrotetraazapentacenes were prepared by gold- or palladium-catalyzed 5-endo-dig cyclization of TIPS-ethynylated dihydro...
Gesehen am 27.02.2023
Keywords: Forschungsdaten; Datenbank